Italy : 2005 Article IV Consultation-Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Italy. (IMF Staff Country Reports; Country Report, 2006)
This 2005 Article IV Consultation highlights that despite the better cyclical outlook, medium-term trends for Italy remain troubling: potential growth is estimated at just 1u percent, as low productivity growth and high domestic costs have led to a steady erosion of competitiveness and export market share. The 2005 fiscal deficit target of 4.3 percent of GDP is estimated to have been met, thanks in part to measures introduced by the authorities. For 2006, the authorities have committed to a deficit target of 3.5 percent of GDP.